A brief theoretical approach on allelopathic potential in plant communities (Research, Society and Development, 2022)
In plant communities, plants can interact positively, negatively, or neutrally. This is a very important feature to ensure survival, in addition to providing information for building knowledge and products to be used in the specific control of some weeds. The objective of this work was to carry out a literature review on the effects of allelopathy on plant communities, which can be observed both in intraspecific and interspecific competitions. Based on the results of the literature, it is likely that allelopathic compounds can alter ecosystem components that, in turn, drive processes and interactions, which modify the composition and dynamics of plant communities. However, a major gap in allelopathy research lies in the lack of methodologies to be applied in the field that demonstrate the role of these compounds in interspecific and community-wide development. Thus, it is necessary that studies that take into account the sources of variation between species, the types of impacts caused on associated species and, mainly, their effects at the community level.